A model of engaging gamification mechanics for achieving MOOC learning outcomes among TVET learners - Mohd Yusoff, Azizul (2020)
Gamification is the integration of game-like design elements into non-game context to engage learners. In tertiary education, researchers and practitioners have been seeking for effective ways to improve student engagement and promote learning. A number of study analyses examining the relationship between MOOC and learning engagement indicated that 25% of learner did not do activities and only 11.7% learner exceed learning goal. This study is conducted to introduce a model of engaging online learning using gamification mechanic (EG-MOOC) in achieving MOOC TVET learning outcomes. There are three objectives to be achieved in this study. The first objective is to determine what are the best appropriate gamification elements for TVET learners, the second objective is to propose a model of engaging online learning using gamification mechanics in achieving MOOC learning outcomes among TVET learners and the third objective is to validate the proposed engaging gamification massive open online courses model. This study applied quantitative methods. In analysis and design phase, the elements of EG-MOOC model were identified through data analysis from Analytical Hierarchy Process Analysis (AHP), documents review and finally validated by five experts. A prototype of EG-MOOC that integrates six gamification elements which are Virtual Goods, Wally’s Game, Trophies-Badged, Rewards, Skill Points and Peer Grading to measure learner’s engagement was implemented in Multimedia Systems subject through Open Learning platform. A total of 138 undergraduates from Bachelor of Computer Science (Interactive Media) in a Universiti Teknikal Malaysia Melaka (UTeM) had participated in a quasi-experiment. A pre-test-post-test design with control and experiment group was set up to examine the effects of gamification mechanics. There were three testing instruments used in this research, namely pre-test and post-test, administrative data from system and online survey of learner perception in gamification system. The research model is tested via Partial Least Squares Structured Equation Model. The findings show that overall model explaining 69.7% variance in learning engagement. Besides that, the result revealed that Badge for Behaviour had strong relationship in a direct effect towards learners learning engagement. Non-parametric test which is Wilcoxon Signal-Ranked Test was run to assess the student performance. Pre-test and post-test findings show that there is a positive effect on student performance. In conclusion, EG-MOOC model has a positive impact in improving learners’ engagement and encourage learners to achieve learning outcomes. Conceptual design of EG-MOOC system can be used as a guideline and model in the produce of gamification-oriented learning model and framework for other student groups.